2019
DOI: 10.1101/807735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Brain to Spine Interface for Transferring Artificial Sensory Information

Abstract: Lack of sensory feedback is a major obstacle in the rapid absorption of prosthetic devices by the brain. While electrical stimulation of cortical and subcortical structures provides unique means to deliver sensory information to higher brain structures, these approaches require highly invasive surgery and are dependent on accurate targeting of brain structures. Here, we propose a semi-invasive method, Dorsal Column Stimulation (DCS) as a tool for transferring sensory information to the brain. Using this new ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, cortical-spinal connections have also been created and show promising evidence for further application. Yadav et al demonstrated that rats could discriminate sensory information delivered by dorsal column stimulation (DCS), as evidenced by recordings from microelectrode arrays that showed this information was transmitted to the brain [62]. Given that Yadav et al stimulated the spinal cord and recorded from the brain, further research could involve spinal cord recordings paired with brain stimulation to transmit sensory information and bypass damaged neural pathways.…”
Section: Cortical ←→ Spinal Neural Bypassesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cortical-spinal connections have also been created and show promising evidence for further application. Yadav et al demonstrated that rats could discriminate sensory information delivered by dorsal column stimulation (DCS), as evidenced by recordings from microelectrode arrays that showed this information was transmitted to the brain [62]. Given that Yadav et al stimulated the spinal cord and recorded from the brain, further research could involve spinal cord recordings paired with brain stimulation to transmit sensory information and bypass damaged neural pathways.…”
Section: Cortical ←→ Spinal Neural Bypassesmentioning
confidence: 99%
“…By utilizing optogenetics in the nucleus incertus of two mice, the mice were able to mimic locomotion with an information transfer rate of 4 bits/second [82]. Lastly, Yadav et al demonstrated a brain-to-spine interface where tactile and artificial sensory information could be decoded by the brain of one rat and delivered to the spinal cord of another rat, with the potential to transmit prosthetic information from the spinal cord to the brain or between brains/spinal cords [62].…”
Section: Inter-subject Neural Bypassesmentioning
confidence: 99%